"These pictures in slow motion passed before us before we could even blink" on photography, revolution, memory, and historical consciousness - Manzanilla, John Paul S. (2024)
Presumably a transparent emanation of the world, the photograph is taken as an authoritative document of important events. Institutions and social groups deploy photos to propagate their versions of reality, while individuals retrieve their pictures to recall memories and forestall overarching narratives that subdue personal interpretations of actions. This essay analyzes photographic renditions of the 1986 EDSA People Power Revolution to understand the protean character of memory and history. Considering photography as the outcome of subjective processes of mediation and representation will help us reflect on the mutability of the past’s interpretation based on the ever-changing preoccupations of the present.
Keywords: Photography - Edsa revolution - 1986; Mass media -- Edsa revolution histoty -- 1986